Methodological Proposal for the Accompaniment and Development of Service+Learning Methodology in Universidad de Las Americas in Chile - Fuentes Rubio, Mario.; Castillo Paredes, Antonio Jonathan. (MDPI, 2022)
Service+Learning (S+L) is an active teaching methodology that enables students to participate in their teaching and learning process, being guided by the teacher. This methodology allows the student to show all the skills, abilities, tools and theoretical-practical knowledge since they are placed at the service of the community partner, which in the case of pedagogies translates into pedagogical practice centers. This transfer must be guided and mediated by the teacher, allowing to provide a response to the requirements of the practice center through the “S+L Booklet”, developed as a methodological proposal for the intermediate practice subject of the Universidad de Las Américas Physical Education Pedagogy career. This instrument takes 15 weeks of weekly development with the proposal, adjustment, development-implementation, monitoring, evaluation and feedback by the students and the teacher of the subject
Keywords: Social education; Educational interventions; Teacher training; Active methodologies university